FINANCING GROWTH AND ITS RISKS IN ISLAMIC BANKING IN INDONESIA, MALAYSIA AND BAHRAIN - AJI KURNIAWAN; AHMAD TOHIRIN (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Purpose-This study aims to analyze financing growth and other factors that affect the risk and stability of Islamic banks in Indonesia, Malaysia and Bahrain. Methodology-This study uses a quantitative approach with a dynamic panel type that uses the Generalized Method of Moment (GMM) method to analyze the impact of financing growth and the factors that affect financing risk and the stability of Islamic banks. Findings-The results showed that faster growth in Islamic bank financing increased non-performing financing which resulted in losses and worsened the stability of Islamic banks. Variables of Capital and Size of the bank moderate the growth of financing which increases the non-performing financing of Islamic Banks. Furthermore, profitability describes the level of efficiency which indicates the low financing risk faced. Implication-These results imply that the growth of Islamic bank financing needs more regulationfurther by strengthening financing risk management as long as financing demand and financing growth increase,by the application of Prudential Banking principles, it is necessary to minimize financing risk and maintain Islamic Bank Stability. Originality-Research on the impact of financing growth on the risk and stability of Islamic banks is still limited. Therefore, this research will contribute to financing growth and the factors that affect the risk and stability of Islamic banks.